Methodology of Nusantara Tafsir: A Study of The Tafsir Turjaman Al-Mustafid by Abdul Rauf Al Sinkili and Tafsir Qur'an Karim by Mahmud Yunus - Rohmanudin, Deden; Yunus, Badruzzaman M. (Mashadiruna Jurnal Ilmu Al-Qurân dan Tafsir, 2023)
Methodological studies within the scope of interpretation are an inseparable study. Because the methodology of interpretation develops according to the development of the interpretation itself. In the archipelago there are two books of commentary that are quite important to study, namely Tafsir Turjaman al Mustafid (classic) and Tafsir Quran Karim by Mahmud Yunus (modern). Departing from this matter, the research will seek to reveal the specific methodology of the interpretation. This study uses a descriptive analysis method with the use of qualitative types. While the data collection techniques using library research techniques. The results of this study reveal the specific methodology between the two interpretations, namely, First, Tafsir Turjaman al Mustafid Abd Rauf there are (1) fadhilah or virtues in the letter, (2) the meaning of the verse by ijmalli, (3) variations of qira'at, (4 ) asbab nuzul and, (5) quoted the opinion of the mufassir. Second, Tafsir Quran Karim by Mahmud Yunus contains (1) editorial translation, (2) global interpretation, (3) includes asbab nuzul, (4) mufradat explanation, (5) linguistic approach and, (6) ibrah or lessons contained in a verse.